Conversion of land use and household livelihoods in Vietnam: A study in Nghe An - Nguyen Tran Tuan (De Gruyter, 2021)
This article describes the relationship between the land use purpose conversion and households’ livelihoods in suburban Vinh City, Nghe An province. In the survey with 170 households losing their land to build the VSIP Nghe An industrial park project, this article shows the double impact of this issue. (1) On the positive side, households’ quality of life in the current period shows a significant improvement. They are living in better conditions with more spacious houses and modern facilities than before. The average income of households increased by 900 USD than before. (2) On the negative side, the unemployment rate increases with women older than 35 years and men older than 40 years. Along with the improper use of compensation received, income sustainability is a doubt for these households’ future.